1968
DOI: 10.1161/01.res.23.6.693
|View full text |Cite
|
Sign up to set email alerts
|

Response of Dogs' Cutaneous Veins to Local and Central Temperature Changes

Abstract: To study the separate actions of peripheral and central temperaturesensitive systems on the cutaneous veins of the dog, a cross-circulation preparation was made in which hindleg and central temperatures could be varied independently. The lateral saphenous vein of a vascularly isolated hindleg was cross-perfused at constant flow; the difference between perfusion and femoral vein pressures was a measure of venomotor activity. With central temperature constant, local cooling of one leg from 47° to 17°C caused the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

1968
1968
1998
1998

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…A potentiated reaction to adrenergic agents during cooling has also been reported for the dog mesenteric artery [16], whereas other studies have shown a depressed affect of noradrenaline [7]. Our experiments thus confirm the observations described previously [22,23], which showed the marked dependency of adrenergic reactions to fluctuations in temperature. The mechanism responsible for the temperature-dependent increase in sensitivity of the mesenteric artery to exogenous noradrenaline is not known from this study.…”
Section: Discussionsupporting
confidence: 92%
“…A potentiated reaction to adrenergic agents during cooling has also been reported for the dog mesenteric artery [16], whereas other studies have shown a depressed affect of noradrenaline [7]. Our experiments thus confirm the observations described previously [22,23], which showed the marked dependency of adrenergic reactions to fluctuations in temperature. The mechanism responsible for the temperature-dependent increase in sensitivity of the mesenteric artery to exogenous noradrenaline is not known from this study.…”
Section: Discussionsupporting
confidence: 92%
“…External application of heat appears to be unsuitable for acute occlusive arterial disease of the periphery. An external supply of heat mainly induces increased perfusion of the skin and the superficial veins with corresponding heat conduction to the surface of the extremity [21]. Therefore, an appreciable rise in temperature in the depth of the afflicted extremity cannot be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to demonstrate the afferent limb of a possible reflex arc from temperature receptors in the limb to the spinal cord and back to the vein via the sympathetic nerves led to the following conclusions (1). If temperature receptors in the limbs were involved, they had to be situated in the vein wall and not in the skin (2). The afferent fibers did not run with other sensory fibers, because cutting the appropriate dorsal spinal roots did not abolish the temperature response.…”
Section: Discussionmentioning
confidence: 99%
“…• Previous studies (1,2) have shown that the superficial limb veins of the dog constrict in response to either a decrease in central temperature or to a cooling of the blood perfusing the vein. Whereas central cooling causes constriction of the cutaneous veins in all the limbs, the constriction with local cooling is confined to the cooled limb.…”
mentioning
confidence: 99%
See 1 more Smart Citation